Resistensi Berbasis Adat: Perlawanan Masyarakat Nagari III Koto, Tanah Datar, Sumatera Barat, Terhadap Rencana Tambang Bukit Batubasi - Fringka, Yulisa (Masyarakat: Jurnal Sosiologi, 2016)
This article discusses the resistance in local societies against mining corporate. This study focuses on conflict approach which is seen if it can be a social movement or not. This study uses the qualitative approach with case study held in Nagari III Koto, West Sumatera. This article shows us that there are seven variables which being the cause of resistance. Norms and custom’s tradition are the most important in determining the forms of resistance. At least there are seven forms of resistance which did by actors in the region until it achieved. Highly legal tradition can be used as a tool to reach the goals of resistance in society. Based on such forms of those resistances, it could be concluded that the resistances of the people in Nagari III Koto are social movement.